Lessons From the Pacific Ocean Portal: Building Pacific Island Capacity to Interpret, Apply, and Communicate Ocean Information - Powers, Molly; Begg, Zulfikar; Smith, Grant; Miles, Elaine (Frontiers in Marine Science, 2019)
The need for improved access to ocean observations for Pacific Island countries and territories has been increasingly recognized over the last decade, particularly in the face of a changing climate. Although more remote sensing and in situ data are available than ever before, however, oceanographic and marine forecasting expertise in the region is limited. To support capacity building in these areas, the Climate and Oceans Support Program in the Pacific (COSPPac) has engaged with partners in the National Meteorological Services (NMS) and other relevant agencies in 14 Pacific Island nations, to identify priorities and to develop tools and training to address these needs. A key tool is the online Pacific Ocean Portal. With a focus on the Pacific Islands region, this website provides ocean data relevant to a range of sectors and applications such as tourism, fishing, shipping, coastal inundation, and environmental management. Via a user-friendly interface, the portal serves up data from a variety of sources including near real-time observations, historical information and forecast data. Training modules have been designed for portal users and delivery has gone hand-in-hand with in-country stakeholder engagement workshops, allowing sector users to make requests for ocean information products. Eight workshops have been delivered from November 2015 to June 2018, training a total of 97 NMS staff and 116 ocean sector stakeholders including port authorities, disaster management, tourism, fisheries, community leaders, and many more. As a result, five Pacific Island NMSs (Tonga, Tuvalu, Kiribati, Samoa, and Vanuatu) are now producing monthly Ocean Outlooks, guided by the needs of in-country stakeholders. Outlooks are tailored for each country and can include forecasts such as sea surface temperature, coral bleaching, and sea level, as well as information about current chlorophyll conditions, wind and wave climate.